A Trip to the ‘Harput Music‘ Museum as an Out-of-School Learning Environment: A Case Study - Türker, Meltem; Bahçeci, Ferhat (Fenerbahçe University, 2024)
Abstract The research utilized a case study approach to investigate the impact of museum visits on out-of-school learning, with a focus on the Harput Music Museum. Gifted students were selected using purposive sampling and given the task of researching Harput culture and a specific musical piece prior to their visit. To enhance engagement, a competition was introduced, with the aim of reinforcing the students' learning through real-time feedback. Semi-structured interviews were conducted to collect students' responses, which were analyzed using thematic content analysis with the help of Maxqda software. The results revealed that although students often find museum visits unexciting, the inclusion of prior research, the competitive element, and the interactive aspects of the trip shifted their perceptions of cultural and social values. The visit significantly heightened students' interest in the historical and musical heritage of Harput, underlining the importance of preserving cultural traditions. Furthermore, the study recommends organizing similar museum visits in other regions and integrating cultural components into various subjects to create a more immersive and engaging learning experience. Keywords: Harput, Museum, Music, History, Out-of-school learning

Bu araştırma, okul dışı öğrenmede müze ziyaretlerinin etkisini incelemek amacıyla nitel araştırma yöntemlerinden durum çalışması deseninin kullanılmasıyla yürütülmüş ve Harput Müzik Müzesi’ne odaklanmıştır. Amaçlı örnekleme yoluyla seçilen üstün yetenekli öğrenciler, ziyaret öncesinde Harput kültürü ve belirli bir müzik parçası hakkında araştırma yapmakla görevlendirilmiştir. Katılımı artırmak için bir yarışma düzenlenmiş ve bu yarışma, öğrencilerin öğrenimlerini anında geri bildirimlerle pekiştirmeyi amaçlamıştır. Öğrencilerin görüşlerini toplamak için yarı yapılandırılmış görüşmeler yapılmış ve bu veriler Maxqda yazılımı kullanılarak tematik içerik analiziyle incelenmiştir. Sonuçlara bakıldığında, öğrencilerin genellikle müze ziyaretlerini sıkıcı bulmalarına rağmen, ön araştırma, yarışma unsuru ve gezinin etkileşimli yönlerinin, öğrencilerin kültürel ve sosyal değerlere bakış açılarını değiştirdiğini ortaya koymuştur. Gerçekleştirilen ziyaret, öğrencilerin Harput’un tarihi ve müzikal mirasına olan ilgisini önemli ölçüde artırmış ve kültürel değerlerin korunmasının önemini vurgulamıştır. Ayrıca, araştırma, benzer müze ziyaretlerinin diğer bölgelerde de düzenlenmesini ve daha etkileyici ve ilgi çekici bir öğrenme deneyimi yaratmak için kültürel öğelerin farklı derslere entegre edilmesini önermektedir.
Okul Dışı Öğrenme Ortamı Olarak ‘Harput Musiki’ Müzesi Gezisi: Bir Durum Çalışması
Keywords: Cultural Studies (Other); Kültürel çalışmalar (Diğer); Developmental Psychology (Other); Gelişim Psikolojisi (Diğer); Applied and Developmental Psychology (Other); Uygulamalı ve Gelişimsel Psikoloji (Diğer); Heritage; Archive and Museum Studies (Other); Kültürel Miras; Arşiv ve Müze Çalışmaları (Diğer)